Strategi Komunikasi Forum Kerukunan Umat Beragama dalam Pengembangan Kerukunan Umat Beragama di Kabupaten Sleman - Wildan Adi Rahman (Dakwah Institut PTIQ Jakarta, 2021)
Sleman Regency is one of the districts that has the highest level of religious diversity in Yogyakarta Province which is ideally vulnerable to harmony conflict between religious people, but in the last four years it is suspected that there is no conflict of religious harmony in the district. The method used in this study is qualitatively descriptive. After research was conducted it was found that, 1) the communication strategy implemented by FKUB Sleman in determining communicators is to choose a trustee of harmony (sub-district level) which is part of the religious organization in accordance with the religion embraced by the guardian of the harmony, the harmony (village level) chosen by the community itself, 2) communication strategies applied in determining the analysis of audience needs by conducting a joint review of four community groups including, permission groups, support groups, opposition groups, and evaluation groups, 3) communication strategies in the preparation of messages used are persuasive, coercive, and educative techniques, 4) communication media used by FKUB Sleman, namely print media such as newspapers, books, and brochures, 5) as for the dynamics of harmony of diverse people in Sleman Regency is currently in a harmonious state.